The Impact of Peer-Assessment on Writing Anxiety in University Students - Czura, Anna (INSTED: Interdisciplinary Studies in Education & Society, 2016)
Foreign language anxiety is one of the most important factors that affect communication in a foreign language. The teacher can lessen or eliminate anxiety by introducing appropriate teaching techniques and creating a positive atmosphere in the language classroom. The study mentioned in this article aims to present the results of a quasi-experiment conducted to verify whether implementing peer-assessment in a group of university students would affect their level of writing anxiety. The data were collected by the means of a questionnaire consisting of both closed-ended and open-ended question. The results indicate that peer-assessment contributed to lowering the level of writing anxiety. What is more, the participants of the study expressed positive opinions about the new form of providing feedback to their writing assignments.